2020
DOI: 10.1038/s41401-019-0333-6
|View full text |Cite
|
Sign up to set email alerts
|

The novel quinolizidine derivate IMB-HDC inhibits STAT5a phosphorylation at 694 and 780 and promotes DNA breakage and cell apoptosis via blocking STAT5a nuclear translocation

Abstract: Sophoridine is a quinolizidine natural product and the exploration of its derivatives has been carried out, and the potent anticancer compound IMB-HDC was acquired. Although previous studies have revealed that some sophoridine derivatives could induce DNA breakage, the underlying mechanisms of inhibition of DNA damage repair (ATR inactivation) and the apoptosis independent of p53, have not been elucidated. Our research reveals a novel DNA response mechanism different from general DNA-damaging agents, and that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Recently, Zhao et al (2020) found that compound 5 ( Figure 5 ) induced DNA breakage and cell apoptosis by blocking STAT5a nuclear translocation and inhibiting STAT5a phosphorylation at 694 and 780. 38 Compared to other derivatives, compound 5 also displayed outstanding water solubility and lower toxicity properties, and its synthesis is straightforward, suggesting that it could be applied as an anti-cancer compound and, therefore, should be explored further.…”
Section: Pharmacological Activities Of Sophoridinementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Zhao et al (2020) found that compound 5 ( Figure 5 ) induced DNA breakage and cell apoptosis by blocking STAT5a nuclear translocation and inhibiting STAT5a phosphorylation at 694 and 780. 38 Compared to other derivatives, compound 5 also displayed outstanding water solubility and lower toxicity properties, and its synthesis is straightforward, suggesting that it could be applied as an anti-cancer compound and, therefore, should be explored further.…”
Section: Pharmacological Activities Of Sophoridinementioning
confidence: 99%
“…37 Recently, Zhao et al (2020) found that compound 5 (Figure 5) induced DNA breakage and cell apoptosis by blocking STAT5a nuclear translocation and inhibiting STAT5a phosphorylation at 694 and 780. 38 Compared to other derivatives, compound 5 also displayed outstanding water solubility and lower toxicity properties, and its synthesis is straightforward, suggesting that it could be applied as an The synthesis of novel sophoridine derivatives using acyclic aryloxy phosphoramidate mustard can greatly improve sophoridine's anti-cancer activity. For instance, compound 6a-6e, containing a phosphoramidate mustard motif substituted at the lactam ring-opened sophoridine skeleton was shown to markedly suppress the viability of S180 and H22 cells (IC 50 = 1.01-3.56 μM).…”
Section: Anti-cancer Of Sophoridine Derivativesmentioning
confidence: 99%
“…STAT5A has been previously designed as a strategic target in the antitumor treatment with IMB-HDC, in which IMB-HDC plays a proapoptotic role by reducing STAT5A phosphorylation and nuclear translocation [ 45 ]. The suppression of STAT5A signaling pathway also promoted apoptosis in osteosarcoma [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lappaconitine inhibits the production of NO, PGE2 and TNF- α by inhibiting NF-kB and MAPK signaling pathways. Paclitaxel skews TAMs towards an immunocompetent profile via TLR4, which might contribute to the antitumor effect of PCX [ 53 , 70 73 , 76 82 , 84 , 85 , 88 , 90 ] MSCs/CSCs VEGF, TRAIL Ptx-PLGA NP-primed MSCs had enhanced sustained Ptx release in the form of free Ptx and Ptx NPs. Ptx transfer from MSCs to glioma cells could induce tumor cell death.…”
Section: Introductionmentioning
confidence: 99%
“…What's more, Sophoridine directly inhibits the cell viability of HepG2 by regulating PTEN/PI3K/AKT, Caspase-3/9 and Matrix metalloproteinase (MMP)-2/9 signal pathways. In addition, Sophoridine also inhibits the migration of macrophages by reducing the expression of CCR2[80][81][82]. Sophoridine evidently activates Hippo and p53 signal pathways to inhibit the occurrence and development of lung cancer[78].…”
mentioning
confidence: 99%